2019
DOI: 10.1021/acsaelm.8b00105
|View full text |Cite
|
Sign up to set email alerts
|

High-Working-Pressure Sputtering of ZnO for Stable and Efficient Perovskite Solar Cells

Abstract: Owing to its high mobility and low sintering temperature, ZnO is a promising electron-transporting layer for flexible and tandem applications of perovskite solar cells. However, ZnO inevitably triggers the degradation of perovskite materials. Such degradation can be inhibited when ZnO films with improved stoichiometry and minimized defects are used. In this work, a high efficiency with substantial stability of ZnObased perovskite solar cells is achieved using a high-workingpressure sputtering technique. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 66 publications
0
12
0
Order By: Relevance
“…This finding correlates well with the detection of the additional carboxylic dangling CO bond (1652 cm −1 ) and OH bond (3381 cm −1 ) in the FT‐IR spectra of the NP‐SnO 2 and Bi‐SnO 2 films (Figure S6, Supporting Information). [ 42,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…This finding correlates well with the detection of the additional carboxylic dangling CO bond (1652 cm −1 ) and OH bond (3381 cm −1 ) in the FT‐IR spectra of the NP‐SnO 2 and Bi‐SnO 2 films (Figure S6, Supporting Information). [ 42,43 ]…”
Section: Resultsmentioning
confidence: 99%
“…It may be noted that the decomposition of perovskite can be started at 358 K [10,11,12]. According to Figure 6, although the operating temperature of PSC without the interface passivation at the ambient temperature 300 K (red dotted curve) increases with applied voltage, it may never reach the decomposition temperature of 358 K because the maximum increase in temperature at the Va=Voc is only about 343 K. However, at Tamb= 320 K, the PSC without interface passivation may reach 358 K at Va 0.85 V (black dashed curve) and may decompose, which will not occur in the passivated PSC.…”
Section: Resultsmentioning
confidence: 99%
“…A high operating temperature may lead to the degradation in PSCs due to the decomposition of the active layer. Conings et al [10,11,12] have investigated the thermal stability of PSCs and found that perovskite may decompose into PbI 2 even at as low a temperature as 85 °C. Philippe et al [11,12,13] have investigated the thermal stability of PSCs by maintaining them for 20 minutes at room temperature, 100 °C and 200 °C and observed that MAPbl3 starts to decompose into Pbl 2 at 100 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides improving optical absorption, the NP‐M13 interlayer also passivated the ZnO ETL by eliminating the dangling hydroxyl (–OH) groups on the surface and improved its surface wettability. [ 34,35 ] A hydrophilic ZnO surface is beneficial to the infiltration of polymers. Indirectly, the NP‐M13 interlayer helped to improve the ohmic contact between ZnO and polymer, thus enabling more efficient charge transport across the ZnO/polymer interface.…”
Section: Figurementioning
confidence: 99%